IMPLEMENTASI PENGGUNAAN QRIS SEBAGAI STRATEGI DIGITALISASI UMKM DALAM MENDUKUNG PARIWISATA BERKELANJUTAN DI DESA SENARU - Mutia, Ainaya; Ramdhini, Dhinda Valentina; Putri, Kharisma Rinjani; Daniyanti, Dyah Eka; Yanti, Karisma; Scabra, Andre Rachmat (Jurnal Wicara, 2025)
Senaru Village is one of the villages located in Bayan Sub-district, North Lombok Regency, West Nusa Tenggara Province, and is a tourist village with significant potential in the tourism and creative economy sectors. Most Micro, Small, and Medium Enterprises (MSMEs) in this village still rely on cash payment systems, which are considered inefficient and make financial recording difficult. Low digital literacy, limited network infrastructure, and a lack of education about digital marketing are barriers to the adoption of modern payment technologies. Therefore, the digitalisation of payment systems through Quick Response Code Indonesian Standard (QRIS) can be a solution to improve transaction efficiency, transparency, and the competitiveness of MSMEs in the tourism sector. This activity aims to introduce and implement QRIS among MSMEs in Senaru Village as a digitalisation strategy to support sustainable tourism and strengthen the local economy. The implementation method includes direct visits to three selected MSMEs based on recommendations from the village government. The results of the activity show an increase in the knowledge and skills of SME actors in using QRIS for daily transactions. Business actors are beginning to get used to recording transactions digitally, so that the payment process becomes faster, more transparent, and more accountable. The implementation of QRIS in Senaru Village has proven to be effective in improving efficiency, transparency, and market access for MSMEs, as well as supporting the sustainability of village tourism.